Impact Evaluation of the Quality of Antenatal Care (ANC) Offered by Health Care Providers at Kintampo North Municipality. - Kwarteng, A.A. (University of Ghana, 2022)
Background Antenatal Care (ANC) is an essential component of safe motherhood programme, involving systematic medical supervision of the pregnant woman until labour or until delivery through elective caesarean section. Adhering to the ANC guidelines, it was expected that maternal mortality issues become solved. However, issues of maternal mortality persist. Objective The study was to assess an impact evaluation of quality ANC offered by ANC nurses in Kintampo North Municipality. Method A cross sectional descriptive study was employed in a quantitative approach. Convenient sampling method was used in selecting 79 nurses and midwives who work in ANC at selected health facilities within the Kintampo North Municipality. Conclusion The data revealed that 87.3% of the total participants‘ responses depicted high knowledge on ANC guidelines, 97.3% showed high knowledge on danger signs associated with pregnancy and 96.3% demonstrated quality ANC practices. The study found that nurses and midwives who work at the ANC in the Kintampo North Municipality have high knowledge level on ANC guidelines and danger signs associated with pregnancy. It was found that nurses and midwives who work at the ANC in the Kintampo North Municipality adhere to quality ANC practices.
MPH. Monitoring and Evaluation
Keywords: Antenatal Care (ANC); Health Care Providers; Kintampo North Municipality